High-contrast imaging at small separations: impact of the optical configuration of two deformable mirrors on dark holes. Issue 1 (10th May 2017) - Beaulieu, M.; Abe, L.; Martinez, P.; Baudoz, P.; Gouvret, C.; Vakili, F.
Abstract: The direct detection and characterization of exoplanets will be a major scientific driver over the next decade, involving the development of very large telescopes that require high-contrast imaging close to the optical axis. Some complex techniques have been developed to improve the performance at small separations (coronagraphy, wavefront shaping, etc.). In this paper, we study some of the fundamental limitations of high contrast at the instrument design level, for cases that use a combination of a coronagraph and two deformable mirrors for wavefront shaping. In particular, we focus on small-separation point-source imaging (around 1 λ/D). First, we analytically or semi-analytically analyse the impact of several instrument design parameters: actuator number, deformable mirror locations and optic aberrations (level and frequency distribution). Second, we develop an in-depth Monte Carlo simulation to compare the performance of dark hole correction using a generic test-bed model to test the Fresnel propagation of multiple randomly generated optic static phase errors. We demonstrate that imaging at small separations requires a large setup and small dark hole size. The performance is sensitive to the amount of optic aberration and the spatial frequency distribution but shows a weak dependence on the actuator number or setup architecture when the dark hole is sufficiently small (from 1 to ≲ 5 λ/D).